Where do people get their news?. (18th January 2019) - Kennedy, Patrick J; Prat, Andrea
SUMMARY: The media industry is unique in its ability to spread information that may influence the democratic process. This influence depends on where and how citizens get their political information. While previous research has examined news production and consumption on specific media platforms — such as newspapers, television, or the Internet — little is known about overall news consumption across platforms. To fill this gap, we use a model of media power and individual-level survey data on news consumption to estimate the potential electoral influence of major news organizations in 36 countries. Our analysis highlights three global patterns: high levels of concentration in media power, dominant rankings by television companies, and a link between socioeconomic inequality and information inequality. We also explore international differences in the role of public service broadcasting.